Dilution of airborne contaminants from through-wall exhausts located on the side of multi-family residential buildings. (15th August 2022) - Kaes, Matthew; Jajal, Nehal; Shahvari, Saba Zakeri; Goebes, Marian; Carter, John; Simon, Austin; Ritter, Jared; Walker, Iain; Clark, Jordan
Abstract: Several models exist for predicting dilution from large rooftop exhausts, but their validity has not been assessed for horizontally directed through-wall exhausts such as those that often exist in new multi-family residential construction. Separation distances derived from rules of thumb or simplified versions of these models are prescribed in ventilation standards, but their appropriateness has not been assessed and they are sometimes difficult to achieve in practice. In order to provide more justifiable separation distances, we conducted a series of wind tunnel experiments and computational fluid dynamics (CFD) simulations measuring dilution of a horizontally-directed exhaust from a test building. We then compared these measurements to existing models and assessed the models' validity for this situation. Lastly, we gathered dilution criteria for several contaminants of interest and used wind tunnel and CFD results along with published emission rates to specify a separation distance that is likely to result in acceptable air quality at neighboring intakes. Results show that mitigation of chronic health concerns from cooking, and smoking in dwelling units, as well as odor concerns from bathrooms, can likely be achieved with separation distances of 5 feet or less. To prevent irritation from smoking in neighboring units, a separation distance of 10 feet is recommended. We did not find that furnace exhaust can be diluted sufficiently with separation distances that are feasible on multi-family buildings. Highlights: Existing dilution models fail to predict dilution of horizontally-directed exhausts. Little dilution happens in the horizontal direction within 15 feet. Furnace exhausts cannot practically be diluted within typical distances. Five feet separation distance is needed for cooking and smoking health concerns. Ten feet is required to mitigate smoking irritation concerns.